NILAI-NILAI PENDIDIKAN KARAKTER DALAM NOVEL SANG PENCURI WARNA KARYA YERSITA (PENDEKATAN PRAGMATIK RESEPTIF) - Paqih Paqih (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2020)
The purpose of this study is to describe (1) the values of social education, (2) the values of religious education, and (3) the values of cultural education in the novelThe Thief of Color Because Allah Loves Yersita's works. The design of this study used a qualitative descriptive method with the Receptive Pragmatic approach. Qualitative methods pay attention to natural data, data in relation to the context of its existence. The results of the study show that the values of social education include character education: teachers as inspirators, understanding children's character, values of national character, education are very important. The values of religious education include prayer, prayer, forgiveness, do not blame each other, friendship, giving names and ihlash. Cultural education values include applying culture, corruption culture, threatening culture, and demonstration culture. Some of the cultures performed by the characters in the novel are a reflection of everyday life.